Design of highly transparent conductive optical coatings optimized for oblique angle light incidence - Nedelcu, N.; Chiroiu, V.; Munteanu, L.; Girip, I.; Rugina, C.; Lőrinczi, A.; Matei, E.; Sobetkii, A. (Applied physics. A, Materials science & processing, 2021)
In this paper, three deposition techniques are combined to create a window material with high average transmission at oblique angles of incidence. Spectrophotometry and ellipsometry measurements, respectively, yield the optical constants n and k . In contrast with other analyses on the subject, a high average transmission, higher than 91% in the 450–900 nm spectral range, is obtained at incident angles of 20–25°. The refractive index and extinction coefficient are determined by the Swanepoel method. The iterative optimization performed using the OpenFilters software leads to an antireflection (AR) multilayer with low reflection and high transmission. The surface quality of the films was characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), which revealed compact, continuous, and smooth films.